Le Musée imaginaire de Jean Dubuffet ? Réflexions sur la documentation photographique dans les archives de la Collection de l’Art Brut - Baptiste Brun (Les Cahiers de l'École du Louvre)
In 1947, while Malraux had the first essay in the Psychologie de l’art series, entitled Le musée imaginaire, published by Éditions Albert Skira, Jean Dubuffet and some associates opened the Foyer de l’Art Brut in the basement of the Galerie René Drouin in the place Vendôme in Paris. The two men, who knew each other, used photographic documentation to assert their conceptions of art. But the global and inclusive aims of Malraux, who made the abstract notion of “style” the common denominator of humanity’s works of art, were replaced by Dubuffet with the specificity of an “art brut” that positioned itself in part against the museum and whose definition he refined through a vast undertaking of exploration and documentation. In this construction, photographic reproduction played an essential role.